Implementation of the Al-Quran and Science Integration Approach at the Asajaya Regional Middle School - Mohd Aderi Che Noh; Fadzila Binti Rahman (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
Integration of Al-Quran and Science (PIQS) was introduced as a hub for enriching students' monotheism elements and playing a role in implementing the Higher Level Thinking Skills (KBAT) element. This study aims to identify the effectiveness of the PIQS approach on the achievement of KBAT and student perceptions in the field of faith. This study was carried out in four high schools in the Asajaya area, and a total of 80 second-year students were sampled for the study. This study uses a quasi-experimental design (Quasi-Experimental Design). The instruments used are pre-test and post-test, which consist of 10 subjective questions to measure students' KBAT in the field of faith. In addition, probing questions were used to measure students' perceptions of the approach used between the control and experimental groups. A total of 40 students in the control group were taught using conventional methods, while 40 students in the experimental group were exposed to the PIQS approach. Data collection for pre and post exams was analyzed using the Statistical Package for the Social Science (SPSS) version 23.0 program. The study results were analyzed using an independent sample t-test to see if there was a significant difference in students' minimum KBAT achievement between the experimental group and the control group in the pre and post exams based on two different approaches in learning the field of faith. The study results show that the minimum post-test achievement for the treatment group is 29.22 higher than the control group, which is 21.57, and the difference between the two is 7.65 points. The investigation results also show that the minimum perception of the PIQS approach is high, which is 44.25, compared to the minimum perception of the traditional approach of 37.25. This study implies that it allows students to understand and explore the field of faith more clearly and can indirectly increase students' KBAT levels.